2000
DOI: 10.1001/jama.283.11.1451
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in the Intensive Care Unit

Abstract: Considering the widespread use of sedation for critically ill patients, more large, high-quality, randomized controlled trials of the effectiveness of different agents for short-term and long-term sedation are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
164
0
15

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(183 citation statements)
references
References 57 publications
4
164
0
15
Order By: Relevance
“…There is evidence in literature that increased sedation is associated with higher risk of postoperative complications [18]. Cost has become a matter of increasing concern, in our current study we reported higher costs in R group compared to S group and this could be due to the less hospital stay and sedative used [19]. This study provide support that the-sedline (PSI)-augmented sedation has an advantageous effects on recovery, ventilation, hemodynamics, hospital stay, inhalational requirements, cost and postoperative complications when compared with Ramsay monitored sedation.…”
Section: Discussionsupporting
confidence: 50%
“…There is evidence in literature that increased sedation is associated with higher risk of postoperative complications [18]. Cost has become a matter of increasing concern, in our current study we reported higher costs in R group compared to S group and this could be due to the less hospital stay and sedative used [19]. This study provide support that the-sedline (PSI)-augmented sedation has an advantageous effects on recovery, ventilation, hemodynamics, hospital stay, inhalational requirements, cost and postoperative complications when compared with Ramsay monitored sedation.…”
Section: Discussionsupporting
confidence: 50%
“…sedation was associated with the prolongation of mechanical ventilation in the ICU. [25,26] Daily interruption of sedation in critically ill patients with mechanical ventilation can result in a decreased duration of mechanical ventilation and a decreased length of ICU stay. [27] Deep sedation and immobility might potentiate ICU-acquired neuromuscular weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Çoğu hastanın mekanik ventilasyonu tolere edebilmesi ve hemodinamik stabiliteyi sağlayabilmesi için sedasyon ve analjezi gereklidir [5] . Yoğun bakımda sedasyonun amacı hastaların konforlu, sakin ve ağ-rısız kalmalarını sağlamaktır.…”
Section: Discussionunclassified